2019
DOI: 10.1136/bmjopen-2019-033224
|View full text |Cite
|
Sign up to set email alerts
|

Access to maternal healthcare services among Indigenous women in the Chittagong Hill Tracts, Bangladesh: A cross-sectional study

Abstract: ObjectivesThis study aimed to estimate the prevalence of, and factors associated with, accessing maternal healthcare services (MHC) by Indigenous women in the Chittagong Hill Tracts (CHT), Bangladesh.DesignThis was a cross-sectional survey among Indigenous women of reproductive age.SettingTwo upazillas (subdistricts) of Khagrachhari hill district of the CHT.ParticipantsIndigenous women (15–49 years) within 36 months of delivery were surveyed about accessing MHC services (antenatal care, delivery and postnatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
0
11
2
1
Order By: Relevance
“…Unlike previous literature, this study found neither travel time nor distance were major barriers to accessing MHC services [52]. This could be because Indigenous women had limited knowledge about existing facility services within their communities and therefore, had not considered the distance [29].…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…Unlike previous literature, this study found neither travel time nor distance were major barriers to accessing MHC services [52]. This could be because Indigenous women had limited knowledge about existing facility services within their communities and therefore, had not considered the distance [29].…”
Section: Discussioncontrasting
confidence: 89%
“…This was a qualitative study involving in-depth interviews with Indigenous women within 36 months of delivery in Khagrachhari district, Bangladesh. This study was conducted as a part of a mixed-method study [29].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anecdotal reports from the CHT estimate the G6PDd prevalence between 20% and 40% (Khan, personal communication), however in hospital based surveys in the same region only 0.6% to 1.4% of patients were G6PDd [25,26]. The significant differences in these estimates may reflect study populations with different ethnic backgrounds, and associated differences in G6PD genetic profiles, or an underlying difference in G6PD activity in patients with and without malaria [15,27]. Understanding whether the prevalence of G6PDd differs significantly between different ethnicities living in the same area is essential in informing decision-makers on whether and how to introduce routine testing for G6PDd into national malaria treatment guidelines.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%